Sistem Informasi Penggajian Karyawan Pada PT. Malka Makarya Selaras Jakarta - Azidah, Nanda Ainnoor; Ariyati, Indah (Journal of Students‘ Research in Computer Science, 2021)
PT Malka Makarya Selaras Jakarta is a human resource management consulting services company. Problems in the salary calculation process such as making payslips and the absence of a company database are only paper document archives, over time there are often typos and lost files. Researchers build an employee payroll information system that is displayed on the company's internal website page where the manager is only a special payroll officer. The software development method in this research is the waterfall model. The results of the study obtained that the salary calculation process can be carried out on the employee payroll information system so as to produce faster and more accurate information, payroll can directly print salary slips as official evidence between the company and employees, payroll information systems as a benchmark for technological progress so as to facilitate the company's performance in decision-making.